Rainfall Characteristics Pattern and Distribution analysis at Tadong East Sikkim - Das, Shaon Kumar; Avasthe, R. K.; Sharma, P.; Sharma, K. (Indian Journal of Hill Farming, 2018)
Sikkim is one of the highest rainfall-receiving states in India. Trends in monthly, seasonal,and annual rainfall on the meteorological station at Tadong, Gangtok were examined inthis study. The year 2009 received lowest amount of annual rainfall (2458.8 mm), whereasthe year 2003 received highest amount of annual rainfall (3740.6 mm) during the period1983-2015. The year 2010 received highest number of rainy days (205 days) but itsprevious year 2009 received lowest number of rainy days (128 days) from 1983-2015. Theaverage or mean annual rainfall was 3088.8 mm and the value of standard deviation wasfound to be 310.5 mm. The year 1986, 1988, 1989, 2006, 2007, 2009 and 2013) receivingrainfall less than 2778.3 mm should be drought years in Tadong. Thus, trend analysis ofrainfall data series for 1983–2015 did showed a clear trend for the region as a whole.